Superovulation of prepubertal and young pubertal gilts with PMSG - ANASTASIADIS (Α. ΑΝΑΣΤΑΣΙΑΔΗΣ) A.; AMIRIDIS (Γ. Σ. ΑΜΟΙΡΙΔΗΣ) G. C.; LYMBEROPOULOS (Α.Γ. ΛΥΜΠΕΡΟΠΟΥΛΟΣ) A. G.; KORONAKI (Α. ΚΟΡΩΝΑΚΗ) A.; VAINAS (Ε. ΒΑΪΝΑΣ) E. (Journal of the Hellenic Veterinary Medical Society, 2018)
The feasibility of application of a standardized protocol for estrous synchronization, superovulation and embryo transfer in young pubertal and pre-pubertal gilts under farm conditions was investigated. Two groups of Large white X Landrace crossbreed gilts were used. Group A (n = 16) consisted of pubertal (>6months old ) animals weighing 100-110 kg while group Β (n=ll) consisted of prepubertal gilts weighing 75-80 kg. Superovulation and estrous synchronization was conducted by intramuscular administration of 1500 IU of PMSG and 750 IU of hCG given 12 and 72 hours after the transfer of the gilts to the service area (hour 0), respectively. At hours 96 and 108 the animals that exhibited estrous behavior (81,3 and 72.7% for groups A and Β respectively) were inseminated with fresh semen from a Large White boar containing 3xl09 progressively moving spermatozoa. Embryo collection took place 48 – 52 hours after the second insemination. No differences were detected in ovarian response, in the number of collected oocytes and in the number of fertilized ova between the two groups 31,5 ±16,9, 25,2±15,8, 17,5±9,9 and 44,6±22,4, 38,5 ±23,2, 21,6 ±9,5 for groups A and Β respectively. The proportion of fertilized ova was significantly higher in group A when compared to the one from group Β (75.7 vs 60.6% for group A and Β respectively, Ρ < 0.05). A negative correlation was also observed between the number of corpora lutea and fertilization rate (P< 0.0005). It is concluded that the present superovulation scheme can be used safely for sufficient embryo production from both prepubertal and pubertal gilts under farm conditions.